Analysis of Conveyance Losses from Tertiary Irrigation Network - Naeem Shah Bukhari Syed; Zhao Shuqi; Muhammad Munir Babar; Rajesh Kumar Soothar (Salehan Institute of Higher Education, 2021)
Irrigation canals are generally made through porous soil formations, since the soil is loose porous media – a huge amount of canal water is lost to conveyance losses. The situation becomes direr when these losses result in non-beneficial losses. The Sindh province of Pakistan has more than 70% saline groundwater, conveyance losses to such areas in the province not only become unusable but also creates water management problems. Perhaps the only cost-effective way to address these losses is canal lining. The present study was conducted in the command area of Belharo distributary, Sindh, Pakistan with an aim to determine the extent of losses from the tertiary irrigated network as these water channels are less considered in the literature with regards of conveyance losses. Using water balance method, conveyance efficiency and conveyance losses at 30% lined and 50 and 75% unlined length of the watercourses was observed. The results revealed that the tertiary irrigation channels face an average of 43% conveyance losses and major proportion of these losses is lost to non-beneficial losses from the study area. The study further suggests 75% lining of watercourses in order to minimize non-beneficial losses. This study also infers that with the use of geo-membrane lining, sizeable amount of fresh water can be saved. Doi: 10.28991/cej-2021-03091756 Full Text: PDF